2013
DOI: 10.1186/1752-4458-7-29
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the psychiatric advance directive in low-resource settings: an exploratory qualitative study in Tamil Nadu, India

Abstract: BackgroundPsychiatric advance directives, a tool to document preferences for care in advance of decisional incapacity, have been shown to benefit persons with mental illness in a number of countries through improving medication adherence, reducing symptoms from escalating in a crisis, accelerating recovery, and enhancing service user autonomy. While concepts such as autonomy are important in a number of high-income country settings, it remains unclear whether tools like psychiatric advance directives are suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…An update to our original search was performed in May 2014, which identified a further five papers meeting our inclusion criteria. 134 138 Although all were small studies focused on specific clinical populations, 134 , 136 , 138 or on variants of care planning, 135 , 137 their data corroborated our synthesis, highlighting the following ongoing barriers to service user involvement: ritualised practices; 136 , 138 insufficient information provision; 134 , 135 , 138 lack of service user confidence, 138 or competence; 135 and professional scepticism. 137 Effective involvement will aIways depend on the skills and competencies of the parties involved, and it is arguable whether all service users and carers possess the necessary skills and confidence to work collaboratively with mental health professionals.…”
Section: Discussionsupporting
confidence: 75%
“…An update to our original search was performed in May 2014, which identified a further five papers meeting our inclusion criteria. 134 138 Although all were small studies focused on specific clinical populations, 134 , 136 , 138 or on variants of care planning, 135 , 137 their data corroborated our synthesis, highlighting the following ongoing barriers to service user involvement: ritualised practices; 136 , 138 insufficient information provision; 134 , 135 , 138 lack of service user confidence, 138 or competence; 135 and professional scepticism. 137 Effective involvement will aIways depend on the skills and competencies of the parties involved, and it is arguable whether all service users and carers possess the necessary skills and confidence to work collaboratively with mental health professionals.…”
Section: Discussionsupporting
confidence: 75%
“…They interviewed 39 clients and 12 caregivers and concluded that introduction of ADs in India might be associated with positive outcome in some users. [ 2 ] Pathare et al . (2015) tried to identify what service users would opt for if they make ADs.…”
Section: Introductionmentioning
confidence: 99%
“…A study from the SCARF foundation shows psychotic patients with a long-term illness were able to make valid PADs irrespective of their education and locality of stay(Kumar et al, 2013). In another 2013 study, patients decided about treatment (passive, active, and collaborative) depending on the situation and decision at hand, and had high levels of self-efficacy(Shields et al, 2013). Another recent study from south India by Pathare and his group investigated service users and their families' opinions about the newLepping et al, 2015).…”
mentioning
confidence: 99%